DEGRADASI ZAT MAKANAN DALAM RUMEN DARI BAHAN MAKANAN BERKADAR SERAT TINGGI YANG DIAMONIASI UREA - Arsyadi Ali (State Islamic University of Sultan Syarif Kasim Riau, 2005)
The research was conducted to know the rumen cegradation of high level crude fiber feedstuffs which were urea ammoniated. Two fistuled bulls, weight 200 kgs and 5.5 years old were used. The treatments were urea amonizations of straw, baggase and wood pClWder followed by 0,6,12,24,48 and 72 hours of incubation. The experiment was analyzed with Randomized Complete Design by 3 x 2 x 6 factorial mode and 2 replication.The result showed that urea ammonizations increased dry matter degradation of straw, b.:gasse and wood pClWder, crude fiber degradation of wood powder and crude protein degradaion of straw and wood powder